Recommendations for Haemodynamic and Neurological Monitoring in Repair of Acute Type A Aortic Dissection - Deborah K. Harrington; Aaron M. Ranasinghe; Anwar Shah; Tessa Oelofse; Robert S. Bonser (Anesthesiology Research and Practice)
During treatment of acute type A aortic dissection there is potential for both pre- and intra-operative malperfusion. There are a number of monitoring strategies that may allow for earlier detection of potentially catastrophic malperfusion (particularly cerebral malperfusion) phenomena available for the anaesthetist and surgeon. This review article sets out to discuss the benefits of the current standard monitoring techniques available as well as desirable/experimental techniques which may serve as adjuncts in the monitoring of these complex patients.